A Review of Islamic Law on the Practice of "Tumpang Rahim" Based on Maqāṣid al-Syarī'ah and Contemporary Scholars - Zulfahmi, Zulfahmi; Asrofi, Asrofi; Suroto, Suroto (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
The practice of Tumpang Rahim (surrogacy) is one of the innovations in reproductive technology that has caused ethical and legal controversy in Islam, especially in the review of maqāṣid al-syarī'ah. This study aims to analyze the validity of interfering wombs based on the principles of maqāṣid al-syarī'ah, especially ḥifẓ al-nasl (nurturing offspring), as well as the views of contemporary scholars. The research method used is normative juridical with a literature study approach. The results of the study show that the majority of contemporary scholars reject the practice of interfering because it involves a third party in the reproductive process, which results in confusion in nasab, guardianship, and inheritance rights. This practice is also considered to bring more maḍarrah than maṣlaḥat, so it is contrary to the principle of maqāṣid al-syarī'ah which emphasizes the preservation of offspring. From the perspective of maqāṣid al-sharī'ah, the desire to have a child through intercession is not an emergency need. In addition, this practice can trigger various problems, including psychological burdens for husbands, wives, and women whose wombs are rented. Therefore, the practice of intercession is considered haram and is not following the purpose of sharī'ah in preserving offspring and avoiding damage.